THE EVOLUTION OF INTERNATIONAL CRIMINAL JUDICIAL COOPERATION AT THE LEVEL OF THE EUROPEAN UNION - Popoviciu, Laura-Roxana (International Journal of Legal and Social Order, 2024)
In this article I have developed the essential aspects related to international judicial cooperation in criminal matters at the European level: the need for cooperation. The development of human society in general, and the development of technology in particular, have increasingly facilitated and determined the development of relations between states. An important aspect of human progress has been the facilitation of the freedom of movement of individuals and goods, which, although it represents a simplification of daily life and an added value, being beneficial to society, has also created the chance for criminals to lose more easily follow. The progress of mankind in all fields has also generated the diversification of forms of violation of the criminal law, which increasingly exceeds the national borders of the states, not infrequently becoming a form of international violation of the criminal law. The increase in international criminality required the mobilization of states in organizing and intensifying the fight against criminality by adopting legal instruments recognized worldwide in an organized framework. International criminal judicial cooperation between states was thus regulated.